The Esoteric Symbolism of Shamanic Trance and Altered States Phenomena - Relic, Ratka (Cambridge Scholars Publishing, 2020)
Bringing together extensive research on psychology, psychophysiology and phenomenology of the shamanic trance and altered states of consciousness, this book represents a cross-cultural approach to the study of shamanism. It discusses Buryat shamanism in Siberia in comparison with Buddhist and Hindu Yogic techniques, as well as other esoteric traditions. The phenomenon of the shamanic trance is here investigated from the esoteric point of view as a form of mystical or religious experience. The book explores the inner feelings and psychic states of the shaman during the trance, describing the in.